IDENTIFIKASI KONTAMINASI BAKTERI PADA TENSIMETER DI RUANG PENYADAPAN DARAH (AFTAP) UDD PMI KOTA YOGYAKARTA - widia rahmatullah (Politeknik Kesehatan Bhakti Setya Indonesia, 2022)
Bacterial contamination that most often occurs is obtained from the environment, can be obtained from the process of taking blood, donors, the process of making components, equipment used and blood storage, and blood distribution. The results of bacterial contamination research found by Lutpiatina (2017) on medical stethoscopes showed that there were 21 (70%) samples of Staphylococcus aureus bacteria and 5 (17%) samples of Pseudomonas aeruginosa, while other bacteria were 4 (13%) samples. The purpose of this study was to determine the gram-positive and gram-negative bacteria that grew on Nutrient Agar (NA) and Mac Concay Agar (MCA) media on a sphygmomanometer in the blood tapping room (AFTAP) PMI Yogyakarta City. The research method used is True Experiment with The Posttest Only Design approach, namely the results of observations provide descriptive information. The results of the study of 30 samples resulted in bacterial growth with the details of 10 samples of Gram Positive cocus bacteria, 13 samples of Gram Negative bacilli and 7 samples of Gram Negative cocus bacteria. The conclusion of this study is that the most common bacteria found from the results of the swab on the sphygmomanometer in the blood tapping room (AFTAP) UTD PMI Yogyakarta City were Gram-negative bacteria with rod-shaped (Basil).